2008
DOI: 10.1007/s10750-008-9671-y
|View full text |Cite
|
Sign up to set email alerts
|

Consistent, long-term change in rotifer community composition across four Polish lakes

Abstract: Few studies exist documenting changes in rotifer communities over long time intervals. Here, we explore seasonal and long-term variation in rotifer communities in four Polish lakes sampled in 1976 and again in 1997. Rarefied, asymptotic species richness did not differ significantly across study years, although values in 1997 tended to be higher. Simpson's and Shannon-Wiener diversity measures provided inconsistent temporal results, with only the former indicating significantly higher richness in 1997. Sorensen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Some studies have suggested that floods lose substantial characteristics in localities where hydrological control is exerted by reservoirs (Kingsford 2000, Dudgeon et al 2006, Steinberg et al 2009); the controlled floods that occur in these managed localities do not produce the same effects as observed under natural conditions. Under regulated conditions, flood characteristics are modified by, for example, reductions in sediment load, large variations in the frequency of the pulse, and reduced amplitudes of water level variations.…”
Section: Macrothrix Elegans Sars 1901 Copepodamentioning
confidence: 99%
“…Some studies have suggested that floods lose substantial characteristics in localities where hydrological control is exerted by reservoirs (Kingsford 2000, Dudgeon et al 2006, Steinberg et al 2009); the controlled floods that occur in these managed localities do not produce the same effects as observed under natural conditions. Under regulated conditions, flood characteristics are modified by, for example, reductions in sediment load, large variations in the frequency of the pulse, and reduced amplitudes of water level variations.…”
Section: Macrothrix Elegans Sars 1901 Copepodamentioning
confidence: 99%
“…The reduction in rotifer abundance associated with the reduction in TP inputs to Loch Leven is consistent with expectations based on earlier studies of eutrophication impacts. These showed that higher levels of rotifer abundance are associated with increasing levels of eutrophication across a range of different lake types and within individual lakes . The results suggest that total rotifer abundance is a good indicator of both eutrophication and recovery, and that it responds more rapidly to change than other determinands that are used to measure change in water quality more routinely, such as TP and chlorophyll a concentrations.…”
Section: Discussionmentioning
confidence: 91%
“…), some of which have not linked the responses of the rotifer communities that they describe to changes in environmental pressures over time (e.g. ).…”
Section: Introductionmentioning
confidence: 99%